Cash Flow Forecasting for Construction Projects using the Markov Chain Model (A Case Study of Construction Company PT X) - Lala Amalia; Embun Suryani; Lalu Hamdani Husnan; Siti Aisyah Hidayati; I Nyoman Nugraha (Cakrawala Repositori IMWI)
This study aims to analyze the cash flow dynamics of PT X’s construction project using the Markov Chain Model. The data used consist of monthly net cash flows for the period from June 2020 to December 2025, which are classified into four states: Severe Deficit, Moderate Deficit, Stable, and High Surplus. The analysis was conducted using a transition probability matrix, steady-state distribution, multi-period probability prediction, and Mean First Passage Time (MFPT). The results of the study show that PT X’s cash flow condition is volatile and is not strongly dominated by any particular state. The steady-state distribution shows that the company’s long-term probability of being in the deficit group, consisting of Severe Deficit and Moderate Deficit, reaches 49.87%, while the probability of being in the non-deficit group, consisting of Stable and High Surplus, reaches 50.12%. These findings indicate that deficit risk and non-deficit opportunities are relatively balanced. Therefore, PT X needs to manage liquidity, cash reserves, receivables, project terms, and working capital in a more adaptive and probability-based manner.